INTERNAL OFFAL OF AYAM PERCOBAANS FED WITH DIFFERENT CONCENTRATIONS OF PROBIOTIC PROBIO-BALI TANI - F.D., Anabokay; Mudita, I M.; Arta Putra, I.G.A. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the Internal Offal of Ayam Percobaans fed with Probio-BaliTani Probiotics with different concentrations. The research was conducted for 5 weeks (35 days) in the farmer's cage of Peguyangan Kaja Village, North Denpasar. The design used in the study was a complete randomized design (CRD) with 7 treatments and 4 replicates. The technical administration of probiotics was carried out in a way: P0 treatment without giving Probio-BaliTani (only given ordinary drinking water), P1 0.025% Probio-BaliTani, P2 0.05% Probio-BaliTani, P3 0.1% Probio-BaliTani, P4 0.5% Probio-BaliTani, P5 1% ProbioBaliTani, and P6 Probio-BaliTani administration with a combination of concentrations. Technical Concentration Combination in P6 is 0-1 week old Ayam Percobaans given 1% Probio-BaliTani, 1- 2 weeks given 0.5% Probio-BaliTani, 2-3 weeks given 0.1% Probio-BaliTani, 3-4 weeks given 0.05%, and 4 weeks old given 0.025% Probio-BaliTani. Variables observed were percentage weight and length of small intestine, appendix, large intestine and percentage weight of proventriculus, ventriculus, liver, gallbladder, heart and spleen. The results showed that the administration of probiotics Probio-BaliTani through drinking water with different concentrations had no significant effect (P>0.05) on the percentage of ventriculus weight (1.61-2.19%), percentage of proventriculus weight (0.40-0.51%), percentage of spleen weight (0.08-0.13%), percentage of colon weight (0, 39-0.49%), length of small intestine (153.25-171.50 cm), length of appendix (28.00-36.00 cm), length of large intestine (25.75-29.50 cm), but significantly influenced (P<0.05) the percentage weight of small intestine (2.25-2.93%), percentage weight of liver (1.67-2.28%) and percentage weight of heart (0.35-0.52%). Based on the results of the study, it can be concluded that the provision of probiotics Probio Bali-Tani with different concentrations (0.025%, 0.05%, 0.1%, of the weekly target body weight) produces the percentage of ventriculus weight, proventriculus weight, appendix weight, spleen weight, colon weight, as well as the length of the small intestine, appendix length and colon length are relatively the same, but the provision of 0.025% Probio-BaliTani probiotics causes a decrease in the percentage of small intestine weight and Ayam Percobaan liver weight.